Earthquake hoax in Ghana: exploration of the Cry Wolf hypothesis - Ishmael D. Norman; Moses Aikins; Fred Binka (AOSIS, 2012)
This paper investigated the belief of the news of impending earthquake from any source in the context of the Cry Wolf hypothesis as well as the belief of the news of any other imminent disaster from any source. We were also interested in the correlation between preparedness, risk perception and antecedents. This explorative study consisted of interviews, literature and Internet reviews. Sampling was of a simple random nature. Stratification was carried out by sex and residence type. The sample size of (N=400), consisted of 195 males and 205 Females. Further stratification was based on residential classification used by the municipalities. The study revealed that a person would believe news of an impending earthquake from any source, (64.4%) and a model significance of (P=0.000). It also showed that a person would believe news of any other impending disaster from any source, (73.1%) and a significance of (P=0.003). There is association between background, risk perception and preparedness. Emergency preparedness is weak. Earthquake awareness needs to be re-enforced. There is a critical need for public education of earthquake preparedness. The authors recommend developing emergency response program for earthquakes, standard operating procedures for a national risk communication through all media including instant bulk messaging.